Reinterpretation of Gender Concept and Its Influence on Preservation of Barong Show Performance in Blora - Cahyono, Agus; Sunarto, Sunarto; Ary, Deasylina da; Prameswari, Nadia Sigi; Guntaris, Endik (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2023)
Barongan Blora is a traditional folk dance in Central Java that has existed since 1830. The passage of time brings up new social conceptions that influence the implementation of Barongan performances, particularly those relating to gender. This research aims to look into the gender roles of Barongan dancers and how they interact with social and cultural components of society. Gender interpretation aims to understand the social construction of men’s and women’s roles in society. These roles include male and female dancers whose motions express diverse traits while maintaining the performance’s significant values. This study employs a qualitative research design with case studies on various Barongan groups in Blora, Indonesia. In May 2023, data was gathered through interviews, observation, and documentation. The results suggest that cat motions dominate the Barongan dance steps, which are supported by strong, energetic, and nimble characters. On the other hand, each character’s movements are tailored to the roles and the dancers who portray them. Male dancers are cast as characters who appear strong and emphasize masculine attributes, such as Barongan, Gembong Amijoyo, Joko Lodro, Untup, and Nayantaka. Meanwhile, female dancers who play male characters, such as Barongan and Jathilan, must be agile, strong, and feminine. Gender distinctions in Barongan performance can be noticed in the movements created. Still, there are no substantial disparities in physical appearance between male and female dancers because both needed a physique corresponding to the characters being played. The Barongan performance also impacts society’s social and cultural features. Regarding social qualities, Barongan embodies the populist traits of the Blora people, which are based on humanist principles. In terms of culture, Barongan Blora has evolved to keep up with changing times, yet it remains and can be appreciated by all levels of society. Due to its uniqueness, Barongan’s preservation is still carried out in line with the times while maintaining cultural values and content in physical and non-physical forms.